Meta-analysis of trichostatin A treatment effects on mouse somatic cell nuclear transfer - GUO, ZHENHUA; LV, LEI; LIU, DI; LIANGWANG, LIANGWANG (The Indian Journal of Animal Sciences, 2019)
Improving somatic cell nuclear transfer (SCNT) efficiency is challenging, and trichostatin A (TSA) has been implemented to improve this technique, but it does not work for porcine and monkey SCNT. Thus, a meta-analysis was done to understand the relationship between TSA and mouse SCNT. Published articles were collected using PubMed and ScienceDirect from 2000 to 2018. Total 15 studies were included that suggest TSA can improve SCNT mouse blastocyst formation and live birth. Most TSA effects studied were on histone deacetylase (HDACs), hence the impacts of TSA on the cytoplasm, specifically cancer signaling pathways, endoplasmic reticulum, and HDACs localization were investigated. It is likely that TSA benefits mouse SCNT because the nucleus is easy to remove. Using fluorescent labeling to remove nuclei and TSA incorporation, SNCT may be improved for pig and monkey studies.